Digital Marketing, Direct Selling, Lokasi, Bauran Promosi, dan Tingkat Penjualan Pasca Covid-19 Pada UMKM Kawasan Teras Malioboro Yogyakarta - Suwita, Citra; Rintasari, Nugraheni (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2024)
The restriction of community activities during the Covid-19 pandemic impacted consumer spending patterns, leading to a decline in sales for MSMEs. Therefore, in addition to direct sales, online sales also play a crucial role. The objective of this study is to analyze the impact of digital marketing, direct sales, localization, and advertising mix on post-Covid-19 sales levels of MSMEs in Yogyakarta, particularly in the Teras Malioboro area. The study population consists solely of MSME members operating in Teras Malioboro, Yogyakarta. The sampling technique used in this research is actual sampling, with a total of 51 MSMEs. The analysis technique employed is multiple linear regression testing. The results indicate that digital marketing, direct sales, localization, and advertising mix simultaneously and partially influence post-Covid-19 sales levels of MSMEs in Yogyakarta, particularly in the Teras Malioboro area.